1900 N.Y. Laws 26 - (:unkn) unknown (My University, 1900)
Ch. 20, art. 2, § 21: Web-footed wild fowl shall not be taken except with a gun fired at arms length without rest. They shall not be fired at from a boat propelled otherwise than by hand or from any boughhouse or floating device used to conceal the hunter if more than fifty feet from shore, or a natural growth of grass or flags. Fowl taken in violation of law shall not be brought ashore, sold or possessed.
Keywords: HUNTING REGULATION